RNA polymerase molecular beacon as tool for studies of RNA polymerase - promoter interactions - Mekler, Vladimir (Methods, 2015)
The molecular details of formation of transcription initiation complex upon the interaction of bacterial RNA polymerase (RNAP) with promoters are not completely understood. One way to address this problem is to understand how RNAP interacts with different parts of promoter DNA. A recently developed fluorometric RNAP molecular beacon assay allows one to monitor the RNAP interactions with various unlabeled DNA probes and quantitatively characterize partial RNAP-promoter interactions. This paper focuses on methodological aspects of application of this powerful assay to study the mechanism of transcription initiation complex formation by Escherichia coli RNA polymerase σ(70) holoenzyme and its regulation by bacterial and phage encoded factors.